K.H UMAR USMAN: TOKOH PERINTIS KEMERDEKAAN INDONESIA DARI TELUK KUANTAN 1912-1989 - Tresha Lendia Pratiwi; Isjoni '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: K.H Umar Usman was Indonesian independence pioneer figure from Teluk Kuantan. The pioneers of independence are those who have struggled to bring Indonesian to independence, being recognize and ratified as a pioneer with a decree of social minister of indonesia. The purpose of this study is to know the biography of K.H Umar Usman, what he had done and his truggle after independence of indonesia. The method used in this study is a historical research consists of four stage, they are heuristics (source collecting), source criticism, interpretation, and historiography. The data was collect from interview and book. The data obtained from interviews and the books were analyzed by using own words. this research wasconducted in teluk kuantan. This research was conducted starting from the issuance of research permiti until this thesis is done. The technique of collecting data used were interview, library research, and documentation. The result showed that K.H Umar Usman was a pioneer of independence based on the decision of the social minister of Indonesian republic with number pol 3/65. The pioneer of independence was given for his struggle against the colonialist. The struggle by K.H Umar Usman was done by religious an do dak’wah. The struggle by K.H Umar Usman is also done in political way occupying several Importand potitions.Key word: K.H Umar Usman, independence pioneer, struggle